Intrinsic calcium resonance and its modulation: insights from computational modeling - Rathour, Rahul Kumar; Kaphzan, Hanoch (Frontiers in Computational Neuroscience, 2025)
Hippocampal neurons generate membrane potential resonance due to specific voltage-gated ion channels, known as resonating conductances, which play crucial physiological roles. However, it is not known whether this phenomenon of resonance is limited to membrane voltage or whether it propagates through molecular signaling components such as calcium dynamics. To test this, we first utilized a single-compartment model neuron to study the oscillatory intrinsic calcium response dynamics of hippocampal model neurons, and the effects of T-type calcium channel kinetics on the voltage and calcium resonance. We found that in the presence of T-type calcium channels, our model neuron sustained a strong calcium resonance compared to voltage resonance. Unlike voltage resonance, calcium resonance frequency was largely independent of conductance magnitude, and the two types of resonance were dissociated, meaning independent of each other. In addition, we studied the effects of A-type K+-channels and h-channels in conjunction with T-type calcium channels on calcium resonance, and showed that these two types of channels differentially affect calcium resonance. Finally, using a multi-compartmental morphologically realistic neuron model, we studied calcium resonance along the somato-apical dendritic axis. Using this model, we found that calcium resonance frequency remains almost constant along the somato-apical trunk for the most part, and only toward its terminal end, the calcium resonance frequency was increased. Nonetheless, this increase was lesser compared to the increase in voltage resonance frequency. Our study opens new horizons in the field of molecular resonance, and deepen our understanding concerning the effects of frequency-based neurostimulation therapies, such as transcranial alternating current stimulation (tACS).